Komunikasi Persuasif Penyuluh Islam dalam Pemberdayaan Masyarakat Desa - Putri Karina Cahyadi; Riyana Khairunnisa Hidayat; Fajri Ilham Syahbani; Eko Purwanto (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
This study examines the persuasive communication practices used by Islamic counselors in empowering rural communities, analyzing the strategies and techniques used to build trust, and evaluating the impact of these communications on community engagement. Using a qualitative methodology through a literature review, the study leveraged systematic data collection from credible sources, including academic journals, theses, and policy documents. Key findings revealed that effective communication relies on the counselor's credibility, which is rooted in the Aristotelian principles of ethos, pathos, and logos. Various strategies, such as repetition with references to the Quran and socio-cultural approaches, were highlighted as crucial in ensuring community understanding and participation. The techniques used ranged from informative to persuasive communication, including both direct and indirect methods of information dissemination. Furthermore, persuasive communication significantly increased participation in empowerment programs by influencing community perceptions and encouraging voluntary engagement based on religious values. The study concluded that Islamic counselors played a significant role in fostering active participation and trust among rural communities, demonstrating the transformative potential of persuasive approaches in community development initiatives. Overall, the effective use of persuasive communication increases both the quantity and quality of community involvement in empowerment efforts.